2014
DOI: 10.1371/journal.pone.0110526
|View full text |Cite
|
Sign up to set email alerts
|

Serotype Distribution and Antibiotic Susceptibility of Streptococcus pneumoniae Strains Carried by Children Infected with Human Immunodeficiency Virus

Abstract: BackgroundWe studied the serotype distribution and antibiotic susceptibility of Streptococcus pneumoniae isolates carried by children infected with HIV in Jakarta, Indonesia.MethodsNasopharyngeal swabs were collected from 90 HIV infected children aged 4 to 144 months. S. pneumoniae was identified by conventional and molecular methods. Serotyping was performed with sequential multiplex PCR and antibiotic susceptibility with the disk diffusion method.ResultsWe identified S. pneumoniae carriage in 41 children (46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 35 publications
3
41
0
Order By: Relevance
“…Direct Gram-staining was performed on this suspension, and the suspension was also cultured onto 5 % sheep blood agar followed by incubation at 37 °C and 5 % CO 2 for 18–20 h. The plate was re-examined after 48 h of incubation [ 11 ]. The alpha-hemolytic colonies growing on the blood agar plate were sub-cultured, followed by optochin susceptibility testing, bile solubility testing, and Gram-staining [ 12 ], using S. pneumoniae ATCC 49619 as positive control for the testing. The remaining CSF specimens were stored at −80 °C until further processing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Direct Gram-staining was performed on this suspension, and the suspension was also cultured onto 5 % sheep blood agar followed by incubation at 37 °C and 5 % CO 2 for 18–20 h. The plate was re-examined after 48 h of incubation [ 11 ]. The alpha-hemolytic colonies growing on the blood agar plate were sub-cultured, followed by optochin susceptibility testing, bile solubility testing, and Gram-staining [ 12 ], using S. pneumoniae ATCC 49619 as positive control for the testing. The remaining CSF specimens were stored at −80 °C until further processing.…”
mentioning
confidence: 99%
“…The S. pneumoniae serotype 6B detected in this study is one of the predominant serotypes in Indonesia [ 12, 29–31 ]. The World Health Organization (WHO) has recommended vaccination with seven-valent pneumococcal conjugate vaccine (PCV7) and 13-valent pneumococcal conjugate vaccine (PCV13) [ 32 ].…”
mentioning
confidence: 99%
“…Today, however, penicillin resistance varies from 5-60% in various parts of the world (13,14). Of particular concern is the increase in multidrugresistant S. pneumoniae strains demonstrating resistance to three or more drug classes (15)(16)(17)(18), which creates substantial concerns about both the efficacy of current antibiotic regimens and the continual development of resistance. In addition, the formation of S. pneumoniae biofilm during colonization provides a barrier to effective antibiotic activity (19)(20)(21)(22)(23), thus limiting complete bacterial clearance and promoting the development of resistance (24,25).…”
mentioning
confidence: 99%
“…Epidemiological data on Streptococcus pneumoniae carriage and invasive disease are currently limited in Indonesia. 6 In the mid 1990s studies reported 21% and 36% of penicillin non-susceptible and erythromycin resistant S pneumoniae, respectively, in Jakarta. 7 In Lombok Island, the prevalence of S pneumoniae carriage was 48% in healthy children, of which all isolates were susceptible to penicillin and cefotaxime and 12% were non-susceptible to sulfamethoxazole or chloramphenicol.…”
Section: Antimicrobial Resistance In Indonesiamentioning
confidence: 99%